ANALISIS KESALAHAN EJAAN BAHASA INDONESIA PADA TUGAS MAKALAH MAHASISWA PROGRAM STUDI TADRIS ILMU PENGETAHUAN ALAM (TIPA) FAKULTAS TARBIYAH DAN ILMU KEGURUAN UNIVERSITAS ISLAM NEGERI DATOKARAMA PALU - Andi Nurfaizah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to examine the form of error in the use of Indonesian Spelling (EBI) on paper assignments for students of the Natural Sciences Tadris Study Program (TIPA), from the Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University Palu. The date in this study is in the form of errors in the use of Indonesian spelling in the paper assignments of semester 1 (one) students of Indonesian language courses. The source of the data in this study was a group paper assignment for semester 1 (one) Indonesian language courses. The results showed that there were 20 errors in the use of capital letters, 10 errors in writing italics, 5 errors in writing number symbols, 15 errors in writing prepositions, 7 errors in writing particles, 5 errors in writing abbreviations, and 5 errors. On punctuation writing, as well as 6 mistakes in writing compound words. Based on results research shows that students in college students Program Traditional Studies of Science Knowledge Semester nature one not yet mastered the technique, especially in the use of Nature Spelling Indonesian (EBI) capital letters, italics